MEMBANGUN BUDAYA RELIGIUS MELALUI KEGIATAN SUPERVISI DI MADRASAH - Subadar, Subadar (JURNAL ISLAM NUSANTARA, 2017)
This paper describes the Role of Supervisor in Building Religious Culture. Teachers are components of human resources that must be fostered and developed continuously in order to perform its functions potentially. Therefore, to improve the quality of education starts from teachers and other education personnel. One of the efforts that can be done is by doing a supervision. Religious culture is one of the objectives of learning Islamic religious education, ie that learners can lead to the aspect of being not only leads to aspects of knowing and doing it. In this case, supervisor support will be given to build a religious culture, considering that one of the goals of the supervisor is the one provided to help teachers become professional, skilled and skilled teachers and able to do more effectively in achieving educational goals.